1985
DOI: 10.1017/s0317167100046564
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind Controlled Pilot Study of Plasma Exchange versus Sham Apheresis in Chronic Progressive Multiple Sclerosis

Abstract: ABSTRACT:Twenty patients with chronically progressive multiple sclerosis (MS) were randomised in a double-blind controlled study to assess the efficacy of plasma exchange therapy. All patients were immunosuppressed with prednisone and azathioprine and underwent either plasma exchange or sham apheresis. The 10 patients in each group were similar in age, sex, duration of disease and degree of disability. Clinical and laboratory responses were assessed immediately following the course of exchange or sham therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…18,[20][21][22] Since the last TTA report, an additional Class II study of azathioprine and plasmapheresis in 11 patients with secondary progressive MS (8 patients completed the trial) concluded that plasmapheresis did not improve outcomes.…”
Section: Cns Demyelinating Diseasementioning
confidence: 99%
“…18,[20][21][22] Since the last TTA report, an additional Class II study of azathioprine and plasmapheresis in 11 patients with secondary progressive MS (8 patients completed the trial) concluded that plasmapheresis did not improve outcomes.…”
Section: Cns Demyelinating Diseasementioning
confidence: 99%
“…(We were able to calculate the number of patients worsening or improving by 1 or more grades on the DSS from the data reported by Hauser et al [12], but not from the figures presented by Tindall et al [lo] or Gordon et al [24].) Separate analyses were conducted on the reported results of neurologic evaluations at 6, 12,24, and 36 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Six identified studies met our selection criteria [3,10,12,13, 22,24]. Their design attributes are summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…In two initial small size studies in 1985 patients with chronic MS were treated with PLEX as an add-on therapy to cyclophosphamide, intramuscular immunoglobulins or steroids and azathioprine [3,4]. The first one showed that significantly more patients in the PLEXgroups stabilized or improved at 5 months, as compared with the sham group.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PLEX was rather ineffective in most of the studies in chronic progressive or secondary progressive MS [3,4]. In purely progressive MS, a study of combination treatment with azathioprine and PLEX in 8 patients with SPMS led to the conclusion that PLEX did not improve clinical outcomes or prevent the formation of Gd-EDPA enhancing lesins in MRI [15].…”
Section: Introductionmentioning
confidence: 99%